Identifying the Challenges and Achievements of Implementing the Antibiotic Stewardship Plan in Qom Hospitals in 2021 - R Babaei; AR Raisi; M Ferdowsi (Armaghane Danesh Bimonthly Journal, 2025)
Background: Controlling the use of antibiotics is necessary to prevent the development of antibiotic resistance in patients. The antibiotic stewardship plan aims to maintain and improve health standards with the systematic design of prescribing antibiotics. This project has been implemented in Iran since 2017. The purpose of the research is to investigate the achievements and challenges of the antibiotic stewardship plan in the hospitals of Qom City. Methods: 21 experts working in Qom hospitals were interviewed. The questionnaire's validity was determined using the CVR method, and its reliability was determined using the Kappa coefficient. Finally, the interviews were coded and analyzed using the grounded theory method. Results: The achievements of the plan include more coordination of the treatment staff, improvement of the treatment method, better monitoring of the consumption and treatment method, and more acceptance of the treatment staff. The challenges of the plan also include causal conditions (weak training, weak infrastructure, lack of specialists, lack of profitability, lack of trust in the plan, weak implementation, and non-compliance with the law), intervening conditions (coronavirus, inconsistency of doctors, time-consuming and weak performance of the active doctor (background conditions) Absence of pharmacists, lack of proper reporting and lack of patient involvement with the plan) strategies (manpower training, technological innovation, more supervision, reassuring doctors, considering financial resources for doctors) and outcomes (improving antibiotic use, reducing drug resistance, reducing Drug use and innovation in the treatment system). Conclusion: The research findings show that the antibiotic stewardship plan's challenges are currently greater than its achievements. However, with the passage of time and the necessary training, the volume of these problems will decrease.